Pereira problem solving - Pereira, L.; Santos, J. (ICOPEV International Conference on Project Economic Evaluation, 2018)
One of the current challenges in organizations is related to decision-making in adverse, uncertain and complex environments. Problem-solving approach is a process of analysis that has been supporting managers’ decision-making. There are several problem-solving tools like the Fishbone diagram, Root Cause Analysis and 5 Why’s that allow an investigation of the problem and its causes. However, due to its limitations, the solutions presented do not always lead to the best results for the organization. The proposed model "Pereira Problem Solving" ensures a better understanding of the problems and an identification of the best solutions. Through the control group technique (10 companies), the research aimed to compare results between the ad hoc process used by managers to seek problem solutions and the "Pereira Problem Solving" process. After implementing the solutions which resulted from each type of approach (ad hoc vs Pereira Problem Solving), the identified key performance indicator was measured to analyze the level of effectiveness of the proposed model.